The realization of e-books for teaching as reflected by by EFL teachers of Islamic Junior High School (MTs) - Nana Priajana; Luqman Baehaqi (Universitas Islam Negeri Palangka Raya, Indonesia, 2012)
This study was aimed at processing empirical data to know the realization e-book program in EFL teaching and learning process as reflected by English teachers of Islamic Junior High School (MTs) in Indonesia. It is a descriptive research of which the approach is a cross sectional survey. The result of this study was expected to be the basis for the government to re-evaluate the implementation of the national project of School Electronic Books (BSE). Based on the result of data analysis, the program of e-books should be revised as considering several factors affecting its insufficient use by the EFL teachers of MTs. The use of E-book in teaching and learning in Indonesia EFL classroom had been beyond the teachers